Energy Efficient Handover Management in Cluster Based Wireless Sensor Network - Mahdi Zareei; Muhammed I. Alghamdi; A.K.M. Muzahidul Islam; Sabariah Baharun; Rahmat Budiarto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Wireless sensors are compact-size, low power, inexpensive devices which are capable to measure local environmental conditions or other parameters such as temperature, acceleration, and forward such information to a sink for proper processing. Wireless sensor networks (WSNs) have been under development by both academic and industrial societies for a while. By moving toward applications such as the area of medical care and disaster response mobility in wireless sensor networks has attracted a lot of attentions. In energy constraint sensor network, mobility handling introduces unique challenges in aspects like resource management, coverage, routing protocols, security, etc. This paper, proposes an energy-efficient mobility-aware MAC protocol to handle node handover among different clusters. The simulation-based experiments show that the proposed protocol has better performance compared to the existing S-MAC method.